The Effect of Technology-Supported Inquiry-Based Learning in Science Education: Action Research - Zeynep Koyunlu Unlu; Ilbilge Dokme (Seyit Ahmet Kıray, 2020)
The general aim of this action research was to offer ways of making science and technology education more effective and solving problems in the related field. The specific purpose was to determine how inquiry-based learning supported by instructional technologies improves students' achievement and develops their scientific inquiry skills. Taking into consideration the literature and the interest areas of the researchers, the inquiry-based 5E instructional model was embedded in a new framework of 4W questions ("What will I learn?", "Why will I learn?", "With what will I learn?", and "What have I learned?") and supported by instructional technologies involving specific stages with standard applications for solving problems. The implementation was carried out at the seventh-grade level in a Turkish middle school in a semester. The participants were a researcher-teacher and six students (two girls, four boys). According to the results, the students' science achievement and scientific process skills developed. This implementation effectively addressed students' affective learning areas, such as their attitudes, motivation, sense of responsibility, and values in relation to the learning environment. It is hoped that the results of this research will offer insights for researchers and practitioners.